1989
DOI: 10.1042/bst0170441
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of sugars across the lysosome membrane

Abstract: Lysosomes are intracellular sites of macromolecule degradation confined by a membrane that localizes hydrolytic enzymes in close proximity to their macromolecular substrates. The monomeric products of digestion then cross the lysosome membrane and enter the cytosol to participate in further cellular metabolism. The mode of metabolite translocation was formerly considered to be diffusion, but latterly evidence has indicated the presence of carriers in the lysosome membrane (for reviews, see Reijngoud & Tager, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Alternatively, if they are suspended in a solution containing a molecule that is not permeable across the membrane at 250 mM concentration, the organelles will remain stable. Lloyd utilized this behavior to evaluate the permeability of lysosomes to various compounds of interest 25,26. In order to evaluate the rupturing of the organelle, the activity of luminal lysosomal enzymes was assessed in the media containing the organelle after addition of a variety of analytes.…”
Section: Methods For Assessing the Sequestration And Resultant Structmentioning
confidence: 99%
“…Alternatively, if they are suspended in a solution containing a molecule that is not permeable across the membrane at 250 mM concentration, the organelles will remain stable. Lloyd utilized this behavior to evaluate the permeability of lysosomes to various compounds of interest 25,26. In order to evaluate the rupturing of the organelle, the activity of luminal lysosomal enzymes was assessed in the media containing the organelle after addition of a variety of analytes.…”
Section: Methods For Assessing the Sequestration And Resultant Structmentioning
confidence: 99%
“…It has been suggested that simple diffusion may play a role in the lysosomal transport of neutral sugars [12,14]. This may be the case for L-fucose transport, accounting for the extremely large Km.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been limited to examination of uptake of sugars, and little information is available about efflux of sugars from lysosomes. Argument persists over the existence of this transport system, and it has been suggested that neutral sugars merely diffuse across the lysosomal membrane [12][13][14]. In addition, transport of L-fucose, a glycoprotein constituent, has not been well studied.…”
Section: Introductionmentioning
confidence: 99%